Anatomy and Pathology of the Ischiorectal Fossa. (15th August 2016) - Arbelo-Cruz, Norman; Lisanti, Christopher; Walker, Kyle; Schwope, Ryan; Bui-Mansfield, Liem T.; Reiter, Michael
Abstract : The ischiorectal fossa is rarely discussed in the radiology literature. Yet, many disease processes may involve this space. The objectives of this article are to review the anatomy of the ischiorectal fossa, to present a practical approach to the differential diagnosis of a lesion within the ischiorectal fossa, and to educate radiologists about the important information that they must provide to surgeons to assist them in the treatment of patients with these disorders.